New developments in biotechnology applied to microorganisms - EFSA Panel on Genetically Modified Organisms (GMO); Ewen Mullins; Jean‐Louis Bresson; Ian Crawford Dewhurst; Michelle M. Epstein; Leslie George Firbank; Philippe Guerche; Jan Hejatko; Francisco Javier Moreno; Hanspeter Naegeli; Fabien Nogué; Nils Rostoks; et al. (EFSA Journal)
Abstract EFSA was requested by the European Commission (in accordance with Article 29 of Regulation (EC) No 178/2002) to provide a scientific opinion on the application of new developments in biotechnology (new genomic techniques, NGTs) to viable microorganisms and products of category 4 to be released into the environment or placed on the market as or in food and feed, and to non‐viable products of category 3 to be placed on the market as or in food and feed. A horizon scanning exercise identified a variety of products containing microorganisms obtained with NGTs (NGT‐Ms), falling within the remit of EFSA, that are expected to be placed on the (EU) market in the next 10 years. No novel potential hazards/risks from NGT‐Ms were identified as compared to those obtained by established genomic techniques (EGTs), or by conventional mutagenesis. Due to the higher efficiency, specificity and predictability of NGTs, the hazards related to the changes in the genome are likely to be less frequent in NGT‐Ms than those modified by EGTs and conventional mutagenesis. It is concluded that EFSA guidances are ‘partially applicable’, therefore on a case‐by‐case basis for specific NGT‐Ms, fewer requirements may be needed. Some of the EFSA guidances are ‘not sufficient’ and updates are recommended. Because possible hazards relate to genotypic and phenotypic changes introduced and not to the method used for the modification, it is recommended that any new guidance should take a consistent risk assessment approach for strains/products derived from or produced with microorganisms obtained with conventional mutagenesis, EGTs or NGTs.